Cell Cycle Genes Are Potential Diagnostic and Prognostic Biomarkers in Hepatocellular Carcinoma. (8th June 2020) - Liping, Xu; Jia, Li; Qi, Chen; Liang, Yang; Dongen, Li; Jianshuai, Jiang
Abstract : Background . The cell cycle pathway genes are comprised of 113 members which are critical to the maintenance of cell cycle and survival of tumor cells. This study was performed to investigate the diagnostic and prognostic values of cell cycle gene expression in hepatocellular carcinoma (HCC) patients. Methods . Clinical features and cell cycle pathway gene expression data were obtained from the Gene Expression Omnibus and The Cancer Genome Atlas databases. Differentially expressed genes (DEGs) were determined by the student t -test between HCC and noncancerous samples. Kaplan-Meier survival, univariate, and multivariate survival analyses and validation analysis were performed to characterize the associations between cell cycle gene expression and patients' overall survival and recurrence-free survival. Results . 47 and 5 genes were significantly upregulated and downregulated genes in HCC samples, respectively. The high expression of BUB3, CDK1, and CHEK1 was associated with increased mortality (adjusted P value = 0.04, odds ratio (OR): 1.89 (95% confidence interval (CI): 1.04-3.46); adjusted P value = 0.02, OR: 2.06 (95% CI:1.15-3.75); and adjusted P value = 0.04, OR: 1.84 (%95 CI: 1.03-3.32), respectively). The expression of PTTG2 and RAD21 was significantly associated with cancer recurrence (adjusted P value = 0.01, OR: 2.17 (95% CI: 1.24-3.86); adjusted P value = 0.03, OR: 1.88[95% CI:1.08-3.28], respectively), while the low expression of MAD1L1 was associated with cancer recurrence (adjusted P value = 0.03, OR: 0.53 (%95 CI: 0.3-0.93)). Conclusions . The present study demonstrated that BUB3, CDK1, and CHEK1 may serve as a prognostic biomarker for HCC patients. PTTG2, RAD21, and MAD1L1 expression is a major factor affecting the recurrence of HCC patients.